2021
DOI: 10.1016/j.jmh.2021.100051
|View full text |Cite
|
Sign up to set email alerts
|

Equity in access to COVID-19 testing for undocumented migrants and homeless persons during the initial phase of the pandemic

Abstract: Introduction The COVID-19 pandemic has excessively affected socially and economically deprived groups of population. There is a dearth of empirical evidence about the effect of policies regulating access to care for such groups. This study aims to document the impact of an equity-based strategy to facilitate access to COVID-19 testing during the initial phase of the pandemic. Materials and methods This cross-sectional study included all outpatients presenting at the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
(28 reference statements)
0
18
0
2
Order By: Relevance
“…We identified differences between community and hospital-based studies regarding variations in pre-existing comorbidities. Based on a community-based sample of participants, three studies reported no difference in the proportion of participants having comorbidities between undocumented migrants and the general population [ 27 , 28 , 42 ]. However, one record-based study reported that all undocumented migrants attending a clinic due to symptoms had chronic comorbidities that worsened the severity and outcome of the infection [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified differences between community and hospital-based studies regarding variations in pre-existing comorbidities. Based on a community-based sample of participants, three studies reported no difference in the proportion of participants having comorbidities between undocumented migrants and the general population [ 27 , 28 , 42 ]. However, one record-based study reported that all undocumented migrants attending a clinic due to symptoms had chronic comorbidities that worsened the severity and outcome of the infection [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Voluntary mass screening at reception centres for asylum seekers in Finland [ 53 ] and Greece [ 41 ] identified multiple COVID-19 outbreaks. Undocumented migrants and homeless persons in Geneva experienced a higher positivity rate for COVID-19 compared to the general population (32.1% vs. 23.6%, p = 0.005) [ 28 ]. In another study, although undocumented migrants with the infection had a comparable proportion of hospitalisations with other population groups [ 28 ], a higher proportion required ICU treatment [ 33 ] and complications attributed to the majority (74.2%) of deaths occurring among undocumented migrants in the U.S. [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some migrant populations (defined as foreign-born individuals) are known to be at risk of underimmunisation 1 , 2 , 3 , 4 and have been involved in recent outbreaks of vaccine-preventable diseases in the EU and European Economic Area (EEA). 5 The severe health inequities exposed by the COVID-19 pandemic, 6 , 7 , 8 , 9 including barriers to accessing vaccination services, 10 have highlighted the need for novel strategies to improve engagement with underimmunised groups, address barriers to COVID-19 vaccine uptake, and facilitate countries in meeting their vaccination targets, relieving their health systems, and reopening their economies. 10 , 11 Emerging evidence shows lower COVID-19 vaccine uptake in some migrant and ethnic minority populations, groups which have been disproportionately affected by the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Migrants are known to be vulnerable to challenges for which other population groups are, to some extent protected from ( Baggio et al., 2021 ). Migrants are found globally in all regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the local population, generally, migrants (both cross-border and internal migrants) are usually poor and have poorer health outcomes than the local populations ( Cantor et al., 2021 ). This could partly be as a result of a systemic inequity of access to available healthcare services ( Burns et al., 2021 ), lack of information about available medical aid, cultural perception of illness that influence health-seeking behaviour and (cultural) as well as language barriers ( Salinas et al., 2021 ; Akhtar et al., 2022 ; Barlow et al., 2022 ; Baggio et al., 2021 ). In addition to these, real or perceived discrimination, unfriendly policies in the local communities and poverty tend to negatively affect health outcomes among migrants ( Garcini et al., 2021 ), Likewise, loneliness and low social support and poor understanding of the health system in the host community have also been cited as factors of inequitable access to healthcare services ( Akhtar et al., 2022 ; Ruiz-Sánchez et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%